Experimental Study on the Cause of Inorganic Scale Formation in the Water Injection Pipeline of Tarim Oilfield - Guihong Pei; Chunyang Wang; Lili Liu (Journal of Chemistry)
Scale formation of water injection pipeline will cause the pipeline to be corroded and increase frictional drag, which will induce the quality and quantity cannot meet the need of oil production process. The cause of scale formation in different oilfield is different because of the complex formation conditions. Taking one operation area of Tazhong oilfield as research object, the authors studied the water quality in different point along water injection pipeline through experiment studies, and analyzed the cause of inorganic scale formation and influence factors. The research results can provide theoretical guidance to anticorrosion and antiscale of oilfield pipeline.